PENGARUH NILAI BAGI MAHASISWA DAN LINGKUNGAN INDIVIDU MAHASISWA TERHADAP PROSES PENGAMBILAN KEPUTUSAN DALAM MEMILIH PERGURUAN TINGGI - Danang Yudhiantoro (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2007)
This research analyzes the effects of customer value to consumer decision in education industry. Customer value is one of many factors, that give effect to choose productor service. Consumers will consider which product or service give the highest value for them. This research analyzes the effect of customer value to consumer decision in the high education industry. The result shows that value gives effect to consumer decision.